2015
DOI: 10.1177/1757913915600195
|View full text |Cite
|
Sign up to set email alerts
|

Culinary efficacy: an exploratory study of skills, confidence, and healthy cooking competencies among university students

Abstract: Factors such as lack of culinary knowledge and skill, financial instability, inadequate access to healthy food options, and other time/lifestyle constraints may have played a significant role in limiting their ability to prepare and consume healthy meals. The findings of this study highlight the importance of designing programmes with effective strategies to motivate and encourage college students to improve their food behaviours and practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 28 publications
4
79
0
3
Order By: Relevance
“…Earlier results reported food skills by sub-groups, without determining which factors were the greatest predictors [2]. The current study examined how much variance in food skills was uniquely associated with selected predictor variables (Supplementary Table 2 1 ).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Earlier results reported food skills by sub-groups, without determining which factors were the greatest predictors [2]. The current study examined how much variance in food skills was uniquely associated with selected predictor variables (Supplementary Table 2 1 ).…”
Section: Methodsmentioning
confidence: 96%
“…The processes involved in personal food production (e.g., planning, budgeting, shopping, preparing, storing, and cleaning up) can be overwhelming for university students with little experience in completing these tasks [1]. Indeed, many prepare meals less than once per week [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still no evidence that the attitude, self-efficacy and the individual cooking knowledge, demonstrated at different levels, have direct effects on the change in people's cooking behaviour [70]. Yet, they consist of elements of analysis that might indicate a possible predisposition to this change, requiring further investigation [68].…”
Section: Classifications Of Foodmentioning
confidence: 99%
“…18 Some suggest that while knowledge on what constitutes balanced diets exists, the problem is the translation into cooking and eating practices. 19 Stress exposure negatively encourages deleterious eating habits with increasing tendencies to snack, skip breakfast, and consume larger portions. 14,18 Research in alcohol use and binge drinking among UK undergraduate (UG) students has found significant numbers of students drinking over the recommended weekly upper limit.…”
Section: Introductionmentioning
confidence: 99%